Cell quality measurement using cloud computing in case of NiCd/NiMH battery study. (13th February 2020) - Lin, Hsiung-Cheng; Wei, Chao-Wei; Chen, Hong-Ming
Currently, 3.6 V 700 mAh NiCd/NiMH battery is the most popular one used in emergency lights or other devices. It is well known that the state of health is related to the battery internal resistance and charging/discharging characteristics. However, the information needed may not be unveiled sufficiently from the manufactory although some certain specifications are provided. To provide users more accurate information, this system proposes an online battery quality measurement system based on two-pulse approach for internal resistance estimation along with long-term charging/discharging life cycle test. The measurement tasks are carried out using the microprocessor that connects with the computer via universal serial bus. Through the data acquisition system, every measured data from the microprocessor can be immediately transmitted to the data server via transmission control protocol/internet protocol. Accordingly, all testing results can be viewed online from the website, and their history record can be also tracked in the database. The experimental results verify that the proposed scheme can perform the quality measurement effectively and accurately.